Implantación de análisis de aceite en motores de combustión interna de ciclo diesel - A, Gabriel (2009)
The condition based maintenance (CBM) and predictive maintenance are strategies that increase the reliability of machinery, enabling us to know their actual condition and lubricant used without disarming it. The main objective of this thesis is to implement the Oil Analysis (OA) in a diesel engine four-stroke cycle, a crude and continuous operation, using the methodology of interpretation called SACODE. The result of the interpretation of OA is complemented by the result of interpretation of various operational parameters of the CBM engine. To develop the methodology SACODE sentencing limits were established by picking up the OA samples every 250 hours. The main anomalies observed in AA trends for one year are presented in report form OA. Send the AA and in parallel, was conducted the monitoring of operational parameters during the last seven months of AA. Also the main anomalies of these parameters were presented in report form CBM. The conclusions are integrated diagnostics engine and lubricant, determining the causes that originate the possible fails and corrective actions to be taken